HRM Perspective on Environmentally Sustainable and Climate-Resilient Economies and Communities in Africa: A Systematic Literature Review - Samuel Bangura; Melanie Lourens (International Journal of Management, Accounting and Economics)
Africa faces significant environmental challenges, including climate variability marked by frequent droughts, floods, and rising temperatures, which threaten economic stability and community resilience. Socio-economic vulnerabilities, particularly in agriculture-dependent sub-Saharan populations, exacerbate these issues. This systematic literature review examines the role of Green Human Resource Management (GHRM) in fostering environmentally sustainable and climate-resilient economies and communities in Africa. It examines the influence of GHRM on sustainability outcomes, effective HRM strategies for resilience, and the barriers to implementation. Adhering to the PRISMA framework, the study synthesizes scholarly literature to address the contributions of GHRM, focusing on green recruitment, training, and employee engagement, alongside barriers such as financial constraints and cultural resistance. Findings revealed that GHRM practices, such as green hiring and training, significantly enhance environmental performance, reducing emissions and resource use in Nigerian and Ghanaian organizations (β = 0.478). In East Africa, GHRM supports climate-smart agriculture, increasing crop yields by 20–30%. However, social sustainability and rural resilience in Central and West Africa remain under-explored. Key barriers include limited resources, low awareness, and weak regulatory frameworks. Grounded on the findings it is recommended that the promotion of green recruitment, digital HRM tools, and partnerships with entities like the Green Climate Fund is significant. Furthermore, the implementation of implementation of awareness campaigns, policy incentives, and change management to overcome barriers is considered important. GHRM is pivotal for sustainable development in Africa, but addressing financial, cultural, and regulatory challenges through targeted strategies is essential to maximize its impact.